KEMASLAHATAN DALAM KONSEP MAQASHID AL-SYAR’IAH - Auffah Yumni (NIZHAMIYAH, 2016)
In today’s globalization and pluralism era with all of its progresses ,moslem and intellectuals are demanded to respond, answer, elaborate the messages in al-Qur’an and Sunnah to solve the problems faced by the society. To do so, it needs an approach to comprehend the Islamic tuitions directing to the invention of substantial and essential values from the Islamic tuitions itself. The approach is the one that emphasizes on syari’ah comprehension especially maslahah dimension.